Susceptibility to primary sclerosing cholangitis is associated with polymorphisms of intercellular adhesion molecule-1. - Yang, X; Cullen, SN; Li, J; Chapman, R; Jewell, D (2004)
BACKGROUND/AIMS: Intercellular adhesion molecule-1 (ICAM-1, CD54) gene polymorphisms have been implicated in the susceptibility to a range of inflammatory diseases, including inflammatory bowel disease (IBD). Primary sclerosing cholangitis (PSC) is an immune-mediated chronic cholestatic liver disease associated with IBD. ICAM-1 is expressed on proliferating bile ducts and interlobular bile ducts in late stage PSC and serum levels of soluble intercellular adhesion molecules are increased in PSC. The aim of this study was to analyse ICAM-1 gene polymorphisms in PSC patients. METHODS: In this study, 104 patients with PSC and 213 healthy controls were recruited from Oxfordshire Caucasians. PCR with sequence-specific primers (PCR-SSP) was used to detect both ICAM-1 biallelic polymorphisms G241R and K469E. The results were controlled for the HLA haplotypes associated with PSC. RESULTS: The E/E frequency of K469E in PSC was 12% (12/104), significantly lower than that in controls (24%, 51/213;P = 0.009; Pc = 0.02; OR, 0.41). The occurrence of the haplotype G241-E469/G241-E469 in PSC was 4% (4/104), significantly lower than the control group (13%, 28/213; P = 0.01; Pc = 0.04; OR, 0.26). There was no difference between PSC and control groups in the frequencies of the genotype R241G or in allele frequencies of K469E. CONCLUSIONS: The E469E homozygote status for ICAM-1 is associated with protection against PSC.